Pattern Of Integration Of Parents And Schools In Instilling Students Affective Values In Islamic Education Learning (PAI) Based On Experiential Learning At SDN Suwayuwo II - Zakiah, Vischa Izza; Yusuf, Achmad; Yusuf, Wiwin Fachrudin (-, 2025)
The purpose of this study is to examine the role of the integration of parents and schools in instilling affective values in students at SDN Suwayuwo II. The method used is a case study with a descriptive qualitative approach that includes observation, interviews, and documentation. The results of the study indicate that collaboration between teachers and parents is crucial to support the character development of students. The Experiential Learning strategy in Islamic Religious Education (PAI) has proven to be an effective strategy in supporting the character development of students. This research emphasizes the importance of parental participation or involvement in the educational process to create an environment that supports the affective development of students. In conclusion, it can be stated that enhancing cooperation between the school and parents is necessary to achieve success in character education. The practical implications of these findings highlight the need for ongoing efforts to improve collaboration between schools and parents in achieving success in character education.